100 contemporary houses - Jodidio, Philip, ....- (Köln : Taschen, 2017)
This title deals with exceptional contemporary houses from Chile to Croatia to China. Designing private homes offers architects more freedom than corporate projects to express their ideas and try out new concepts. Conceiving living spaces is not without its own set of challenges, for which architects are forever looking for innovative solutions-rethinking the way we inhabit our home and live our daily lives is all part of the job when designing a house. Nowadays environmental concerns have become crucial in building sustainable structures, changing the playing field quite profoundly. This two-volume publication rounds up 100 of the world's most interesting and pioneering homes from the past decade, featuring a host of talents both new and established, including John Pawson, Richard Meier, Shigeru Ban, Tadao Ando, and Zaha Hadid.
Woningbouw ; Engels - Duits - Frans
Keywords: Architectuur ; 2000-.